PAPATEAN: Representational Musical Composition of the Story of the Murder of Missionary A. A. van De Loodstrecht in Bori', Toraja - Saputra, Julian; Picanussa, Branckly; Tika Lestari, Dewi (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2024)
The musical composition "Papatean" is based on the story of the murder of the first missionary in Toraja, namely A. A. van de Loodstrech (called Anton) in 1917. Studying history is certainly important because it is full of values??for a better future. After Anton's death, the growth of the congregation in the Toraja Church continued to improve, until it spread internationally. Apart from that, the creation of this musical work aims to remember and appreciate the struggle and dedication of Anton and his wife, who have given their entire lives to God and the Toraja people. Their arrival brought the Gospel as well as the beginning of education in Toraja. The theory used in producing this work is about musical composition, musical harmony, instruments, and program music including narratives, vocals, and scales. The musical instruments used are the Lembang Flute, Piano, Violin, Viola, Violoncello, Contrabass, Floor, Cymbals, Chimes, and Vocals. The method used is the creation method, with several stages, namely (1) Data collection stage (2) Idea stage (3) Exploration stage (4) Implementation stage (5) Formation stage. The work "Papatean" was worked on in three parts, namely part I: Petamba (A, B), part II: Sitiro Lindo (A, B), and part III: Papatean (A, B, C, D).